Unexpected Lack of Deleterious Effects of Uranium on Physiological Systems following a Chronic Oral Intake in Adult Rat. (12th February 2014) - Dublineau, Isabelle; Souidi, Maâmar; Gueguen, Yann; Lestaevel, Philippe; Bertho, Jean-Marc; Manens, Line; Delissen, Olivia; Grison, Stéphane; Paulard, Anaïs; Monin, Audrey; Kern, Yseult; Rouas, Caroline; et al.
Abstract : Uranium level in drinking water is usually in the range of microgram-per-liter, but this value may be as much as 100 to 1000 times higher in some areas, which may raise question about the health consequences for human populations living in these areas. Our purpose was to improve knowledge of chemical effects of uranium following chronic ingestion. Experiments were performed on rats contaminated for 9 months via drinking water containing depleted uranium (0.2, 2, 5, 10, 20, 40, or 120 mg/L). Blood biochemical and hematological indicators were measured and several different types of investigations (molecular, functional, and structural) were conducted in organs (intestine, liver, kidneys, hematopoietic cells, and brain). The specific sensitivity of the organs to uranium was deduced from nondeleterious biological effects, with the following thresholds (in mg/L): 0.2 for brain, >2 for liver, >10 for kidneys, and >20 for intestine, indicating a NOAEL (No-Observed-Adverse-Effect Level) threshold for uranium superior to 120 m g/L. Based on the chemical uranium toxicity, the tolerable daily intake calculation yields a guideline value for humans of 1350 μ g/L. This value was higher than the WHO value of 30 μ g/L, indicating that this WHO guideline for uranium content in drinking water is very protective and might be reconsidered.